Correlation of finite state multi-rotor dynamic inflow models with a high fidelity viscous vortex particle method - Guner, F.; Prasad, J.V.R.; Sankar, L.N.; Peters, D.; He, C. (My University, 2018)
Finite state inflow models have been developed from potential flow theory to predict inflow distributions for single rotor con1gurations. Superposition of velocity or pressure potentials associated with individual rotors has been proposed for arriving at inflow models for multi-rotor configurations. In this study, fidelity assessment of finite state inflow models arrived at using pressure and velocity potential superposition methods for two tandem rotor configurations is considered. Physical wake effects, such as wake contraction and viscous wake dissipation, that are not inherently included in potential flow theory are added to both Pressure Potential Superposition Inflow Model (PPSIM) and Velocity Potential Superposition Inflow Model (VPSIM). In addition, new mass flow parameter formulation for VPSIM is proposed to match with one used in PPSIM. Using this formulation, it is shown that PPSIM and VPSIM have similar steady-state inflow distributions. For model fidelity assessment, the developed finite state inflow models are compared against a high fidelity numerical model known as Viscous Vortex Particle Method (VVPM). Differences in rotors uniform, fore-to-aft and side-to-side inflow components between the models are quantitatively analysed in hover and forward flight. Contour plots of inflow distributions are also provided for qualitative comparison. In addition, effects of inflow distribution and interference velocities on flapping angle predictions are discussed.